Theory of exciton transfer and diffusion in conjugated polymers. - Barford, W; Tozer, O (American Institute of Physics Inc., 2014)
We describe a theory of Förster-type exciton transfer between conjugated polymers. The theory is built on three assumptions. First, we assume that the low-lying excited states of conjugated polymers are Frenkel excitons coupled to local normal modes, and described by the Frenkel-Holstein model. Second, we assume that the relevant parameter regime is ℏω < J, i.e., the adiabatic regime, and thus the Born-Oppenheimer factorization of the electronic and nuclear degrees of freedom is generally applicable. Finally, we assume that the Condon approximation is valid, i.e., the exciton-polaron wavefunction is essentially independent of the normal modes. The resulting expression for the exciton transfer rate has a familiar form, being a function of the exciton transfer integral and the effective Franck-Condon factors. The effective Franck-Condon factors are functions of the effective Huang-Rhys parameters, which are inversely proportional to the chromophore size. The Born-Oppenheimer expressions were checked against DMRG calculations, and are found to be within 10% of the exact value for a tiny fraction of the computational cost. This theory of exciton transfer is then applied to model exciton migration in conformationally disordered poly(p-phenylene vinylene). Key to this modeling is the assumption that the donor and acceptor chromophores are defined by local exciton ground states (LEGSs). Since LEGSs are readily determined by the exciton center-of-mass wavefunction, this theory provides a quantitative link between polymer conformation and exciton migration. Our Monte Carlo simulations indicate that the exciton diffusion length depends weakly on the conformation of the polymer, with the diffusion length increasing slightly as the chromophores became straighter and longer. This is largely a geometrical effect: longer and straighter chromophores extend over larger distances. The calculated diffusion lengths of ~10 nm are in good agreement with experiment. The spectral properties of the migrating excitons are also investigated. The emission intensity ratio of the 0-0 and 0-1 vibronic peaks is related to the effective Huang-Rhys parameter of the emitting state, which in turn is related to the chromophore size. The intensity ratios calculated from the effective Huang-Rhys parameters are in agreement with experimental spectra, and the time-resolved trend for the intensity ratio to decrease with time was also reproduced as the excitation migrates to shorter, lower energy chromophores as a function of time. In addition, the energy of the exciton state shows a logarithmic decrease with time, in agreement with experimental observations.